Find the vertices of a triangle, the midpoints of whose side are(3,1),(5,6,),(-3,2)
Answers
Answered by
129
aloha user!!
----------------
we have to find the vertices of a triangle.
for the given midpoints of sides are:
(3,1)
(5,6)
(-3,2)
------------------------------------------------------------------------------------------
[tex] \frac{x1 + x2}{2} = 3 =\ \textgreater \ x1 + x2 = 6 [/tex]
-----------------------------------------------------------------------------------------
![\frac{y1 + y2}{2} = 1 =\ \textgreater \ y1 + y2 = 2 \frac{y1 + y2}{2} = 1 =\ \textgreater \ y1 + y2 = 2](https://tex.z-dn.net/?f=+%5Cfrac%7By1+%2B+y2%7D%7B2%7D+%3D+1+%3D%5C+%5Ctextgreater+%5C++y1+%2B+y2+%3D+2)
----------------------------------------------------------------------------------------
![\frac{x2 + x3}{2} = 5 =\ \textgreater \ x2 + x3 = 10 \frac{x2 + x3}{2} = 5 =\ \textgreater \ x2 + x3 = 10](https://tex.z-dn.net/?f=+%5Cfrac%7Bx2+%2B+x3%7D%7B2%7D+%3D+5+%3D%5C+%5Ctextgreater+%5C++x2+%2B+x3+%3D+10)
---------------------------------------------------------------------------------------
![\frac{y2 + y3}{2} = 6 =\ \textgreater \ y2 + y3 = 12 \frac{y2 + y3}{2} = 6 =\ \textgreater \ y2 + y3 = 12](https://tex.z-dn.net/?f=++%5Cfrac%7By2+%2B+y3%7D%7B2%7D+%3D+6+%3D%5C+%5Ctextgreater+%5C++y2+%2B+y3+%3D+12)
--------------------------------------------------------------------------------------
![\frac{x1 + x3}{2} = -3 =\ \textgreater \ x1 + x3 = -6 \frac{x1 + x3}{2} = -3 =\ \textgreater \ x1 + x3 = -6](https://tex.z-dn.net/?f=+%5Cfrac%7Bx1+%2B+x3%7D%7B2%7D++%3D+-3+%3D%5C+%5Ctextgreater+%5C++x1+%2B+x3+%3D+-6)
-------------------------------------------------------------------------------------
![\frac{y1 + y3}{2} = 2 =\ \textgreater \ y1 + y3 = 4 \frac{y1 + y3}{2} = 2 =\ \textgreater \ y1 + y3 = 4](https://tex.z-dn.net/?f=+%5Cfrac%7By1+%2B+y3%7D%7B2%7D+%3D+2+%3D%5C+%5Ctextgreater+%5C++y1+%2B+y3+%3D+4)
-------------------------------------------------------------------------------------
now,
by elimination:
x1 + x2 = 6
x1 + x3 = -6
-----------------
- - +
----------------
x2 - x3 = 12 --------------------(1)
by elimination of (1) and x2 + x3 = 10 { from above }
x2 - x3 = 12
x2 +x3 = 10
----------------
2x2= 22
x2= 11
putting the value of x2 in any of the equation above:
x1 + x2 = 6
x1 + 11= 6
x1 = 6 - 11
x1 = -5
now putting the value of x1 in any of the equation we get:
x1 + x3 = -6
-5 + x3 = -6
x3 = -6 + 5
x3 = -1
again by elimination of y1 + y3 = 4 and y1 + y2 = 2
y1 + y3 = 4
y1 + y2 = 2
---------------
- - -
---------------
y3 - y2 = 2--------------------(2)
now by elimination of (2) and y3 + y2 =12 { from above }
y3 - y2 = 2
y3 + y2 = 12
-----------------
2y3 = 14
y3 = 7
now putting the value of y3 in any of the equation we get:
y3 + y2 = 12
7 + y2 = 12
y2 = 12 - 7
y2 = 5
at last, putting the value of y2 in any of the equation:
y1 + y2 = 2
y1 + 5 = 2
y1 = -3
----------------------------------------------------------------------------
hope it helps :^)
----------------
we have to find the vertices of a triangle.
for the given midpoints of sides are:
(3,1)
(5,6)
(-3,2)
------------------------------------------------------------------------------------------
[tex] \frac{x1 + x2}{2} = 3 =\ \textgreater \ x1 + x2 = 6 [/tex]
-----------------------------------------------------------------------------------------
----------------------------------------------------------------------------------------
---------------------------------------------------------------------------------------
--------------------------------------------------------------------------------------
-------------------------------------------------------------------------------------
-------------------------------------------------------------------------------------
now,
by elimination:
x1 + x2 = 6
x1 + x3 = -6
-----------------
- - +
----------------
x2 - x3 = 12 --------------------(1)
by elimination of (1) and x2 + x3 = 10 { from above }
x2 - x3 = 12
x2 +x3 = 10
----------------
2x2= 22
x2= 11
putting the value of x2 in any of the equation above:
x1 + x2 = 6
x1 + 11= 6
x1 = 6 - 11
x1 = -5
now putting the value of x1 in any of the equation we get:
x1 + x3 = -6
-5 + x3 = -6
x3 = -6 + 5
x3 = -1
again by elimination of y1 + y3 = 4 and y1 + y2 = 2
y1 + y3 = 4
y1 + y2 = 2
---------------
- - -
---------------
y3 - y2 = 2--------------------(2)
now by elimination of (2) and y3 + y2 =12 { from above }
y3 - y2 = 2
y3 + y2 = 12
-----------------
2y3 = 14
y3 = 7
now putting the value of y3 in any of the equation we get:
y3 + y2 = 12
7 + y2 = 12
y2 = 12 - 7
y2 = 5
at last, putting the value of y2 in any of the equation:
y1 + y2 = 2
y1 + 5 = 2
y1 = -3
----------------------------------------------------------------------------
hope it helps :^)
Answered by
54
hope it's helped you...
Attachments:
![](https://hi-static.z-dn.net/files/d22/79a291be328dc2fbf3e9e770dae94172.jpg)
![](https://hi-static.z-dn.net/files/d21/a232c349f697f1059e074bc4413faf31.jpg)
![](https://hi-static.z-dn.net/files/d61/c3864261beec21a7982d0a5204d4bec7.jpg)
![](https://hi-static.z-dn.net/files/d66/9126d2abb622b66e09cdc107645193c1.jpg)
![](https://hi-static.z-dn.net/files/dbd/216b4b834d6bbd844393260d578738e6.jpg)
Similar questions
Hindi,
9 months ago
Computer Science,
9 months ago
Science,
1 year ago
Math,
1 year ago
Science,
1 year ago